Harm reduction strategies in acute care for people who use alcohol and/or drugs: A scoping review. - Daniel Crowther; Janet Curran; Mari Somerville; Doug Sinclair; Lori Wozney; Shannon MacPhee; Annette Elliott Rose; Leah Boulos; Alexander Caudrella (PLoS ONE)
Background People who use alcohol and/or drugs (PWUAD) are at higher risk of infectious disease, experiencing stigma, and recurrent hospitalization. Further, they have a higher likelihood of death once hospitalized when compared to people who do not use drugs and/or alcohol. The use of harm reduction strategies within acute care settings has shown promise in alleviating some of the harms experienced by PWUAD. This review aimed to identify and synthesize evidence related to the implementation of harm reduction strategies in acute care settings. Methods A scoping review investigating harm reduction strategies implemented in acute care settings for PWUAD was conducted. A search strategy developed by a JBI-trained specialist was used to search five databases (Medline, Embase, CINAHL, PsychInfo and Scopus). Screening of titles, abstracts and full texts, and data extraction was done in duplicate by two independent reviewers. Discrepancies were resolved by consensus or with a third reviewer. Results were reported narratively and in tables. Both patients and healthcare decision makers contributing to the development of the protocol, article screening, synthesis and feedback of results, and the identification of gaps in the literature. Findings The database search identified 14,580 titles, with 59 studies included in this review. A variety of intervention modalities including pharmacological, decision support, safer consumption, early overdose detection and turning a blind eye were identified. Reported outcome measures related to safer use, managed use, and conditions of use. Reported barriers and enablers to implementation related to system and organizational factors, patient-provider communication, and patient and provider perspectives. Conclusion This review outlines the types of alcohol and/or drug harm reduction strategies, which have been evaluated and/or implemented in acute care settings, the type of outcome measures used in these evaluations and summarizes key barriers and enablers to implementation. This review has the potential to serve as a resource for future harm reduction evaluation and implementation efforts in the context of acute care settings.